Interpretation of gravity data to delineate the subsurface structures and reservoir geometry of the Aluto–Langano geothermal field, Ethiopia. (July 2021) - Mulugeta, Bekele Dejene; Fujimitsu, Yasuhiro; Nishijima, Jun; Saibi, Hakim
Highlights: A Bouguer anomaly map of the Aluto-Langano geothermal field was generated using a Bouguer density of 2.49 g/cm 3 . The high magnitude plots obtained from the edge enhancement by the HD method outline the lateral mass inhomogeneities. The high gravity anomaly observed between the AJFZ and Bobesa is related to shallow, high-density material interpreted as a dike or as the top of intrusive rocks that are denser than the underlying molten material. Abstract: The Aluto–Langano geothermal field is located within the central-southern part of the Main Ethiopian Rift, about 200 km southeast of Addis Ababa. This study analyzes gravity data to define the geometry of the geothermal reservoir and subsurface geological structures controlling the geothermal system. A Bouguer anomaly map of the area was generated using a Bouguer density of 2.49 g/cm 3, which was obtained from the gravity dataset using different optimization methods. In order to highlight the structures of interest in the calderic system, a regional-residual separation was conducted. The map produced shows two dominant high Bouguer anomalies underlying Aluto caldera associated with the presence of basaltic rocks and the occurrence of fumarolic activity. Analysis of horizontal gradients of gravity data showed that the area is characterized by the presence of high gradient anomalies associated with geothermal manifestations. A 3-D gravity model for assessing the geothermal heat source architecture within the Aluto caldera area is also presented. The model was constrained using the estimated densities of rock cuttings obtained from drilled wells. The results from 3-D modeling imaged a high-density body at depth surrounded by a less-dense body (∼2.55 g/cm 3 ), which is interpreted to be the geothermal reservoir. The model was then interpreted together with surface manifestations, lithology, and geological structures. The less-dense body found west of the Adonsha fault lineament could be the expression of the second reservoir, which is likely deeper than the productive reservoir found along the NNE–SSW trending structure (i.e., the Artu Jawe Fault Zone) in the central area.